1994
DOI: 10.1128/iai.62.11.4727-4738.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of a Bordetella pertussis serum resistance locus

Abstract: We have characterized a new virulence factor in Bordetella pertussis: serum resistance. Compared with Escherichia coli HB101, wild-type B. pertussis was relatively resistant to classical-pathway, complement-dependent killing by normal human serum. However, a mutant of B. pertussis (BPM2041) which is less virulent in mice and which has Tn5 lac inserted in a previously uncharacterized bvg-regulated gene was found to be at least 10-fold more susceptible to serum killing than the wild type. We have named this locu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(118 citation statements)
references
References 55 publications
2
115
0
1
Order By: Relevance
“…In a previous report, we showed that the capacity of B. pertussis to survive killing by the classical pathway of complement is regulated by the bvgAS locus with the products of the brk locus (BrkA and BrkB) contributing to a substantial amount of the resistance [2]. In this report, we examine the role of other bvg-regulated virulence factors in mediating serum resistance.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…In a previous report, we showed that the capacity of B. pertussis to survive killing by the classical pathway of complement is regulated by the bvgAS locus with the products of the brk locus (BrkA and BrkB) contributing to a substantial amount of the resistance [2]. In this report, we examine the role of other bvg-regulated virulence factors in mediating serum resistance.…”
Section: Introductionmentioning
confidence: 87%
“…All strains and plasmids are listed in Table 1. All plasmids were mobilized from Escherichia coli into B. pertussis using the suicide vector system described previously [2]. To facilitate this process, pUW2138, containing a Gent r -oriT cassette that was surrounded by the BamHI to SalI multiple cloning sites of pBluescript, was constructed.…”
Section: Strains and Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously mentioned, KM22 harbors a brkA gene that is predicted to be expressed as a full-length functional protein, whereas the brkA gene in RB50 is annotated as a pseudogene (62). For B. pertussis, BrkA has been shown to confer resistance to antibody-mediated complement lysis (63,64). Similar to RB50, KM22 harbors the genes encoding lipopolysaccharide (LPS) and an O-antigen (62).…”
Section: Discussionmentioning
confidence: 99%